Bronchoscope saline injection method (ME Hejazi Method) in ruptured peripheral and central pulmonary hydatid cysts: a case series - Hejazi, Mohammad Esmaeil; Tekantapeh, Sepideh Tahsini; Maddahi, Saeede (Faculty of Medicine, Trisakti University, 2018)
BackgroundThis paper mainly focuses on patients with ruptured pulmonary Echinococcus granulosus infections (alveolar hydatid disease), who suffered from ruptured alveolar hydatid cyst. In this study we aimed to remove these ruptured central and peripheral pulmonary hydatid cysts by the bronchoscopic saline injection method (ME Hejazi method). Case descriptionIn this retrospective study, we evaluated eight patients from an endemic area who were non-surgically treated for ruptured pulmonary hydatid cysts at Imam Reza hospital between 2016-2017. By the bronchoscopic saline injection method (ME Hejazi method), we extracted the entire hydatid cysts of all patients by fiber optic bronchoscopy for the detachment of the underlying membrane from the cavity wall. There were three female and five male patients, with a mean age of 40 Â± 23 years (range 17â€“63 years). Ruptured cysts were located in the peripheral (2) and central (6) parts of the lungs. All of our experiences have been successful without any complications and residual cyst membrane. During the follow-ups, clinical and radiological recovery were seen in these patients.ConclusionsIn the peripheral ruptured hydatid cysts, accurate recognition and location of the cyst is essential and the blind approach is not recommended because it needs several bronchoscopic interventions. Therefore the Hejazi method will be a beneficial and suitable alternative method for surgery in the treatment of patients with ruptured pulmonary hydatid cyst with cyst membrane adhesions.